Personal Data Protection in the Era of Artificial Intelligence: A Critical Review of Indonesia's Regulatory Readiness Based on OECD Principles - Nendy Akbar Rozaq Rois; Hariyadi Fajar Nugroho (CV. Cognispectra Publishing, 2025)
Purpose of the Study: This study aims to evaluate the readiness of Indonesian law in regulating personal data protection in the era of artificial intelligence (AI), by highlighting the conformity of national regulations to international standards, especially the OECD Principles and regulations of developed countries such as the European Union. Methodology: A normative-juridical approach with a qualitative comparative method was used, analyzing Law No. 27 of 2022 (PDP Law) and related instruments. The OECD Principles on AI served as an evaluative framework. The analysis was structured in four stages: (1) identifying OECD principles; (2) mapping provisions in Indonesian law; (3) analyzing regulatory gaps; and (4) comparing with selected jurisdictions (EU, Japan, Singapore, Brazil, India). Case studies were used to illustrate practical implications. Results: The results of the study show that although several aspects such as the principle of consent and data security have been accommodated in the PDP Law, there is still a legal gap in terms of liability for AI violations, algorithm audits, and transparency of automated decisions. Comparison with regulations of developed countries highlights substantial gaps in the protection of data subject rights. Applications of This Study: This study can be used as a normative and practical reference for policy makers in designing a legal framework that is adaptive to the development of AI technology, while increasing legal awareness among technology developers and other stakeholders. Novelty/Originality of This Study: This study offers a critical approach to AI regulation in Indonesia using the OECD Principles as an evaluative parameter, and identifies aspects of the law that have not been widely studied, such as the mechanism for objecting to automated decisions and the right to be forgotten in the context of artificial intelligence